2006
DOI: 10.4049/jimmunol.176.11.7015
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Capacity of Immune Cells to Cause Tissue Injury Mediates Kidney Ischemic Preconditioning

Abstract: Ischemic preconditioning (IP) is a well-established phenomenon, and the underlying mechanisms of IP are thought to involve adaptive changes within the injured tissue. Because one of the main functions of immune cells is to harbor memory, we hypothesized that circulating immune cells could mediate IP by responding to an initial ischemia reperfusion injury (IRI) and then mediate decreased injury after a second IRI event. C57BL/6 mice underwent 30 min of bilateral renal clamping or sham operation. At 5 days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 23 publications
4
40
1
1
Order By: Relevance
“…These data are consistent with previous data in kidney IRI (13) and liver IRI (14) that lymphocytes could play a deleterious or protective role in IRI. Furthermore, recent data support a protective role in splenic lymphocytes when harvested 5 days after kidney IRI to confer an "ischemic preconditioning"-like protection when transferred to wild-type mice when they undergo IRI (35). The current data do not identify which particular cell type could be responsible for this effect or whether either earlier or later time point KMNC have a different effect.…”
Section: Discussioncontrasting
confidence: 43%
“…These data are consistent with previous data in kidney IRI (13) and liver IRI (14) that lymphocytes could play a deleterious or protective role in IRI. Furthermore, recent data support a protective role in splenic lymphocytes when harvested 5 days after kidney IRI to confer an "ischemic preconditioning"-like protection when transferred to wild-type mice when they undergo IRI (35). The current data do not identify which particular cell type could be responsible for this effect or whether either earlier or later time point KMNC have a different effect.…”
Section: Discussioncontrasting
confidence: 43%
“…This is supported by our finding that lipid peroxidation (a marker of iron-mediated injury/ferroptosis) is reduced in hepcidin-treated mice subjected to IRI. 52 Previous studies have suggested an important role of the spleen [43][44][45] and liver 53 in the pathophysiology of renal IRI. We demonstrate that IRI induces hepatosplenic iron export, which likely contributes to the pathogenesis of renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Splenic macrophages play a sentinel role in systemic iron homeostasis. Because splenic iron content decreases after renal IRI, we examined the expression of ferroportin in splenic macrophages.…”
Section: Hepcidin Prevents Iri-induced Ferroportin Upregulation and Smentioning
confidence: 99%
“…These data suggest infiltrating T cells have a complex role in the different phases of IRI. The protective role of splenic lymphocytes 5 days after renal IRI was also demonstrated when transferred to wild type mice with IRI [63]. However, the particular cell type responsible for the aforementioned protective effects has not been identified yet.…”
Section: Different Roles Of T Cell Subsets In Irimentioning
confidence: 92%